2018
DOI: 10.1155/2018/3485967
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Characteristics Influencing Level of Awareness of Aflatoxin Contamination of Feeds among Livestock Farmers in Meru District of Tanzania

Abstract: Aflatoxins occurrence in feeds challenges human and animal health. Farmers' awareness status of these toxins has an effect on their level of exposure. The study assessed the influence of socioeconomic characteristics of farmers on their awareness of aflatoxin contamination of feeds. Data were collected from 258 households and analysed by SPSS program for descriptive statistics and association between socioeconomic characteristics and awareness of aflatoxin contamination of feeds. Over seventy percent of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
3
20
4
Order By: Relevance
“…Sorting and removing visibly defective panicles and grains is an important critical control point for reducing mycotoxin contamination in farm produce. However, visible grain mold may indicate mycotoxins presence, but still very high levels are possible without any noticeable effect on appearance or smell (Ayo et al., 2018 ). In the present study, caregivers suspected the presence of fungal toxins in sorghum if the grains were discolored, had an off‐smell or bitter taste, and they used these features during panicles or grains sorting.…”
Section: Discussionmentioning
confidence: 99%
“…Sorting and removing visibly defective panicles and grains is an important critical control point for reducing mycotoxin contamination in farm produce. However, visible grain mold may indicate mycotoxins presence, but still very high levels are possible without any noticeable effect on appearance or smell (Ayo et al., 2018 ). In the present study, caregivers suspected the presence of fungal toxins in sorghum if the grains were discolored, had an off‐smell or bitter taste, and they used these features during panicles or grains sorting.…”
Section: Discussionmentioning
confidence: 99%
“…The study on the farmers’ knowledge of fungal toxins showed that 62% of dairy farmers had never heard of the level of aflatoxin in the milk sample. Low knowledge and unclear concept about aflatoxins are common in many developing countries, which may allow high aflatoxin exposure through contaminated feeds leading to human disease (Ayo et al., 2018 ). Dairy farmers with awareness about the level of aflatoxin in the milk sample may have information on the source and will protect feed and cows from AFB1 exposure and ultimately safeguard milk from contamination.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, A study by Ayo et al. (2018) found that aflatoxin awareness was deficient among uneducated and socially unexposed farmers in Tanzania. Similar low awareness levels are reported from Ethiopia and Uganda (Guchi, 2015; Nakavuma et al., 2020).…”
Section: Current Aflatoxin‐contamination Prevention Methodsmentioning
confidence: 99%